Post Operative Pain Management and Patient Satisfection : Experience at a Tertiary Care Hospital (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: Pain is an inevitable part of the postoperative experience. Current study was designed to assess the pattern of analgesic use, the adequacy of post operative pain control by documenting pain scores and patient satisfaction by documenting the pain perception score of the postoperative patients 48 hours after surgery.Materials and methods: This was a formative research and includes a mix of descriptive cross-sectional study carried out in the Department of Gynecology and Obstetrics, General Surgery and Orthopedics Surgery of Chattagram Maa-O-Shishu Hospital Medical College (CMOSHMC) during the month of January, 2018 to July, 2019.Results: A total of 180 patients underwent surgery were included in this study. Baseline data were collected both retrospectively and prospectively. Only analgesic used immediately after operation in three departments were Pethidine (100%). Diclofenac sodium suppository were used in appendectomy and cesarean section (50/60, 83%) and (26/60, 43%) respectively. Mostly, Diclofenac Sodium IV (55/60, 91%) was used in lower limb surgery. The maximum pain score were 5.3 (SD=2.3), 5.6 (SD =1.9), and 6.1 (SD =1.3) during coughing in the first 8 hour and minimum pain score 2.4 (SD =1.0), 2.2 (SD = 0.8) and 1.7 (SD=1.3) at rest 48 hours after cesarean section, appendectomy and lower limb surgery respectively. But pain score eventually increased during coughing 48 hours after surgery. After 48 hours of surgery maximum pain perception score 3.9 (SD = 0.9) in lower limb surgery and minimum perception score were 3.5 (SD =1.8) in cesarean section. Majority of the appendectomy patient (76%) satisfied with pain management where as only 43% satisfied in case of cesarean section.Conclusion: This study enabled the researchers to get a precise picture of the current state of POPM in different hospitals, as well as identify particular needs for improving such practices in health care facilities and implementing an educational intervention in order to improve the post operative pain management.Chatt Maa Shi Hosp Med Coll J; Vol.20 (2); July 2021; Page 69-73